Influence of the pH on the corrosion crotection of epoxy-silica-zirconia sol-sel soatings spplied on EN AW-6063 aluminium alloy - Fontinha, I. R. (2014)
Aluminium alloys of 6000 series can suffer severe corrosion in polluted (acidic) and/or marine environments and in contact with alkaline media like fresh cementitious materials. Therefore, architectural aluminium components are often coated, what requires its surface pre-treatment. Organic-inorganic hybrid (OIH) sol-gel coatings have been proposed as an effective, environmental compliant new pre-treatment for aluminium coating. In this work, an epoxy-silica-zirconia sol-gel coating was synthesized and applied on EN AW-6063 alloy. Cerium nitrate was incorporated as corrosion inhibitor. Cerium doped and undoped OIH coatings were exposed to neutral, acidic (pH~3) and alkaline (pH~10) chloride solutions. Electrochemical impedance spectroscopy (EIS) and SEM/EDS characterization of coated samples revealed that the best performance is achieved in the neutral and the worst in the acidic solution. In the alkaline solution, the cerium doped coatings exhibited much better anticorrosive performance than the undoped ones, clearly evidencing the beneficial role of the corrosion inhibitor in this media.